Amsal 1:7 sebagai Fondasi Pendidikan Spiritual Kristen: Rekonstruksi Pedagogis bagi Pembentukan Karakter dan Kematangan Spiritual - Eston Warani (STT Bala Keselamatan Palu, 2026)
This study aims to implement the values of Proverbs 1:7 in Christian spiritual education to foster character formation and spiritual maturity. In the era of information disruption, spiritual education faces the challenge of secularism, which separates intellectual intelligence from moral foundations. Using a qualitative-descriptive method with a literature study approach, the findings reveal that the “fear of the Lord” is not merely a sense of fear, but an ontological orientation that produces character integrity, emotional-spiritual maturity, and ethical commitment. The study concludes that Proverbs 1:7 plays a significant role in shaping students’ character integrity and spiritual maturity. The concept of the “fear of the Lord” cannot be reduced to a mere emotional response of fear, but must be understood as an existential disposition that directs the whole of human life toward God. Proverbs 1:7 holds a crucial role in Christian spiritual education. The value of the “fear of the Lord” serves as a foundation for forming character, humility, and spiritual habits among learners. True knowledge is rooted in a relationship with God. Practically, this implies that Christian spiritual education should not be limited to the transmission of knowledge, but must also emphasize life transformation that results in mature and integrative character formation. Abstrak: Penelitian ini bertujuan mengimplementasikan nilai-nilai Amsal 1:7 dalam pendidikan spiritual Kristen untuk membangun karakter dan kematangan spiritual. Di era disrupsi informasi, pendidikan spiritual menghadapi tantangan sekularisme yang memisahkan kecerdasan intelektual dari fondasi moral. Menggunakan metode kualitatif-deskriptif dengan pendekatan studi pustaka, hasil penelitian menunjukkan bahwa